Politik Identitas dan Negosiasi Kebhinekaan dalam Ruang Publik Digital Indonesia - Ahmad Ridwansyah Perdana; Nurlaila Oktaviani Safitri; Muhammad Syahril Anwari (Nalar Bhinneka: Jurnal Humaniora, 2026)
Identity politics has intensively developed in Indonesia’s digital public sphere alongside the expanding use of social media. This study aims to analyze patterns of pluralism negotiation occurring on digital platforms and the dynamics of collective identity formation amid Indonesia’s diverse society. A critical discourse analysis method was applied to social media content from Twitter/X, Instagram, and YouTube during the period 2023–2025, involving 1,200 purposively selected content items. The findings reveal that ethnicity- and religion-based identity politics dominates digital discourse, yet negotiation mechanisms also emerge that generate spaces for pluralism dialogue. Four dominant patterns were identified: identity polarization, symbolic resistance, inclusive negotiation, and national narrative reconstruction. This study concludes that Indonesia’s digital public sphere is contested yet retains potential for social integration when managed through equitable digital literacy.